2011
DOI: 10.1080/10942910903453397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma Irradiation on Total Phenolic Contents and Antioxidant Activities ofSatureja Hortensis, Thymus Vulgaris, andThymbra Spicatafrom Turkey

Abstract: In this study, the effect of gamma irradiation on the total phenolic content and antioxidant activity of Satureja hortensis, Thymus vulgaris, and Thymbra spicata was evaluated. Plants irradiated in a 60 Co irradiator to 0, 1.2, 3.0, and 5.1 kGy at 25 • C. Control and irradiated samples were extracted with methanol. The antioxidant activity of methanol extracts was determined using phosphomolybdenum assay and the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging method. The total phenolic content in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
(40 reference statements)
1
16
2
Order By: Relevance
“…Brandstetter, Berthold, Isnardy, Solar, and Elmadfa (2009) reported similarly to our findings that the TPC of thyme extracts was not affected by irradiation at 10 kGy. Gumus, Albayrak, Sagdic, and Arici (2011) reported a decrease in the TPC of methanol extract of thyme after irradiation at 5.1 kGy, which does not agree with our results on thyme.…”
Section: Total Antioxidant Activity and Phenolic Contentcontrasting
confidence: 99%
“…Brandstetter, Berthold, Isnardy, Solar, and Elmadfa (2009) reported similarly to our findings that the TPC of thyme extracts was not affected by irradiation at 10 kGy. Gumus, Albayrak, Sagdic, and Arici (2011) reported a decrease in the TPC of methanol extract of thyme after irradiation at 5.1 kGy, which does not agree with our results on thyme.…”
Section: Total Antioxidant Activity and Phenolic Contentcontrasting
confidence: 99%
“…reported that the water-soluble extract from savory (S. hortensis) plant possesses exploitable antioxidant properties, and that the extracts were capable of inhibiting the formation of TBARS. On the other hand, Gumus et al (2011) also determined that irradiated or nonirradiated S. hortensis possessed excellent antioxidant activity and 2,2-diphenyl-1-picrylhydrazyl radical-scavenging activity. This activity observed in this study and previous studies may be related to the antioxidant properties of its secondary metabolites (Kosar et al 2003;.…”
Section: Resultsmentioning
confidence: 99%
“…They are used as culinary herbs and in folk medicine to treat various ailments based on the different plant activities. [4,7] Three species inhabit the territory of Serbia: Satureja montana L. (western Serbia), Satureja subspicata Bartl. ex Vis.…”
Section: Introductionmentioning
confidence: 99%